2022
DOI: 10.1299/jbse.21-00261
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effect of aneurysm model material on coil contact force and catheter movement

Abstract: To ensure safe coil embolization for cerebral aneurysms, it is important to investigate the contact force between a coil and an aneurysm wall. Therefore, in our previous study, we developed an experimental system for measuring the contact force between a coil and an aneurysm biomodel. However, because the aneurysm model was made of silicone rubber, its physical properties, such as the friction coefficient, differed from those of aneurysms in vivo. Therefore, in this study, we made an aneurysm model using poly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Experiments using more complex vascular models made of silicone rubber [29,[35][36][37][38][39], acrylic [40], poly(vinyl alcohol) hydrogel [25][26][27][30][31][32][33], and elastomer-hydrogel skin multilayers [9,28] that mimic living tissue have also been conducted. 3D printers are widely used to prepare biomodels and can easily fabricate mold copies of the vascular tree, which is subsequently embedded in a liquid resin that solidifies into a solid biomodel.…”
Section: Complex Shapesmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments using more complex vascular models made of silicone rubber [29,[35][36][37][38][39], acrylic [40], poly(vinyl alcohol) hydrogel [25][26][27][30][31][32][33], and elastomer-hydrogel skin multilayers [9,28] that mimic living tissue have also been conducted. 3D printers are widely used to prepare biomodels and can easily fabricate mold copies of the vascular tree, which is subsequently embedded in a liquid resin that solidifies into a solid biomodel.…”
Section: Complex Shapesmentioning
confidence: 99%
“…Biomodels that mimic various types of vasculature [9,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] can be used to test new endovascular medical devices and teach techniques to medical personnel; they also allow the practice and planning of procedures before treatment without exposing patients to X-rays. Moreover, biomodels are more economical and ethical compared to human cadavers and animals.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the calculation and experimental results for validation of the simulation system showed that the trajectories and contact forces of the experimental and calculated medical devices tips had the same tendencies. Furthermore, this experimental apparatus can be used not only for validation of the numerical analyses but also as a simulation system that includes a mechanism to move a catheter, a guidewire, and a coil, and to reproduce the catheterization (Oishi et al, 2022;Takashima et al, 2021Takashima et al, , 2017Takashima et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%